Metal-Cation-Directed de Novo Assembly of a Functionalized Guest Molecule in the Nanospace of a Metal—Organic Framework. - Baiyan Li; Yiming Zhang; Dingxuan Ma; Tianliang Ma; Zhan Shi; Shengqian Ma (Journal of the American Chemical Society, 2014)
In this work, a new strategy is developed to encapsulate a metal-functionalized guest molecule into a metal-organic framework (MOF) via metal-cation-directed de novo assembly from the component fragments of the guest molecule. This strategy, as illustrated in proof-of-principle studies on the de novo assembly of metal(II) phthalocyanine molecules into bio-MOF-1, can circumvent some drawbacks of existing approaches for encapsulating guest molecules into MOFs, such as inaccessibility for larger guest molecules due to limitations of the MOF window size and disruption of the MOF framework structure by functionalized guest molecules. Overall, this work provides a general yet versatile approach for encapsulating a broader range of metal-functionalized guest molecules into MOFs for various applications.